Advantages and Disadvantages of Introduction to the Polish Legal Order of a Simple Joint-Stock Company as a New Type of a Commercial Company - Katarzyna MALINOWSKA-WOZNIAK (Communications of International Proceedings, 2021)
The purpose of this paper is to present the outline of the legal construct of a simple joint-stock company as a new type of a commercial company, and also to assess the advantages and disadvantages of introducing provisions that regulate the operation of such a company in the Polish legal order. The discussion is carried out through the interpretation of applicable laws by analysing the normative regulation included in the Polish Commercial Companies Code (along with amendments that are to enter into force on 1 July 2021). After the research, a thesis was formulated that a simple joint-stock company in the Polish legal order should not become a new type of a commercial company, but it should rather be introduced to the Polish Commercial Companies Code as a certain type of a joint-stock company. Moreover, when creating the provisions on a simple joint-stock company the Polish legislator should not trigger a revolution in the commercial companies law. The introduced changes result in the creation of a new capital company which does not fit typologically within the existing classification into partnerships and capital companies, because a simple joint-stock company bears the features of a partnership and a capital company alike. The entry into force of provisions on a simple joint-stock company, however, has many advantages. First of all, entrepreneurs who conduct economic activity in Poland will have a greater choice as to the organizational and legal form of their business activity.
Keywords: Simple Joint-Stock Company; Commercial Company; Simple Share Capital